Banco Comercial Português: the first decade. 1985-1995 - Faria, Miguel Figueira de (2015)
In 1995, we celebrated the tenth anniversary of the foundation of the Banco Comercial Português (BCP). The activities planned included publishing a book to commemorate the first ten years of the bank and its respective group.